COMPOSICIÓN DE LA DIETA DE PELLONA HARROWERI (FOWLER) (PICSES: PRISTIGASTERIDAE) EN LA GUAJIRA, CARIBE COLOMBIANO (Boletín de Investigaciones Marinas y Costeras, 2016)
This study provides quantitative information on digestive tract content of Pellona harroweri caught on the Guajira shelf at a depth of 20 m. Preferential prey are crustaceans, mainly copepos and luciferids.